Congenital syphilis. Guidelines for the diagnosis and treatment. - D’Antuono, A.; Zauli, S.; Bardazzi, F.; Ismaili, A.; Negosanti, F.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Syphilis can severely affect pregnancy, being responsible for spontaneous abortion, intrauterine growth delay and perinatal death. The newborns of affected mothers can be asymptomatic or present variable clinical symptoms and signs. The latter can be misdiagnosed by a non skilled physician. The asymptomatic newborns can be affected and require a specific treatment or can be perfectly healthy and present antibodies passively transmitted by their mother. These different conditions require a different diagnostic and therapeutic approach.